2008
DOI: 10.1080/13504860701596745
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Volatility: Option Pricing using a Multinomial Recombining Tree

Abstract: We treat the problem of option pricing under the Stochastic Volatility (SV) model: the volatility of the underlying asset is a function of an exogenous stochastic process, typically assumed to be meanreverting. Assuming that only discrete past stock information is available, we adapt an interacting particle stochastic filtering algorithm due to Del Moral, Jacod and Protter (Del Moral et al., 2001) to estimate the SV, and construct a quadrinomial tree which samples volatilities from the SV filter's empirical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In preparation for the task of option pricing, we adjust a genetic-type particle filtering algorithm by Del Moral et al (2001, [10]) adapted by Florescu and Viens (2008, [13]) in a stochastic volatility setting with no memory, in order to estimate the empirical distribution of the volatility. In the sequel, following the approach in [13], we use a multinomial recombining tree algorithm for option pricing. Using simulated data we show that this algorithm performs well and captures the underlying memory of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In preparation for the task of option pricing, we adjust a genetic-type particle filtering algorithm by Del Moral et al (2001, [10]) adapted by Florescu and Viens (2008, [13]) in a stochastic volatility setting with no memory, in order to estimate the empirical distribution of the volatility. In the sequel, following the approach in [13], we use a multinomial recombining tree algorithm for option pricing. Using simulated data we show that this algorithm performs well and captures the underlying memory of the system.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that when p is close to 1 6 the option values obtained are stable even with few replications (Figure 4 in Florescu and Viens (2008)). In this paper we set p = 0.135 throughout the algorithm.…”
Section: Discussionmentioning
confidence: 93%
“…ϕ t models the stochastic volatility process. It has been proved that for any proxy of the current stochastic volatility distribution at t the option prices calculated at time t converge to the true option prices (Theorem 4.6 in Florescu and Viens (2008)). When using Stochastic volatility models we are faced with a real problem when trying to come up with ONE number describing the volatility.…”
Section: Issues With Cboe Procedures For Vix Calculationmentioning
confidence: 99%
See 2 more Smart Citations